A conceptual management reference model to guide industry 4.0 implementation in steelmaking plants - Silva, Fernando Henrique da Fonseca (2022)
The theme Industry 4.0 (i4) has great relevance for the global iron and steel sector leading to expectations for competitiveness and operational efficiency increase and also new businesses development through technology transformation. Despite the i4 potential, relatively few academic works have been dedicated to iron and steel sector. Furthermore, it is being reported in the literature, difficulties faced by organizations to implement Industry 4.0 in practice. One way to structure and guide Industry 4.0 implementation is through the use of Industry 4.0 reference management models based on maturity assessment concept. The main objective of this work is to design, evaluate and validate a descriptive management reference model for Industry 4.0 implementation in steelmaking industries. The chosen methodology to be applied is the Design Science Research (DSR) and it was adopted the method for the construction of empirically grounded and validable reference models proposed by Ahlemann and Gastl (2007). The proposed conceptual model is composed of nine dimensions and 54 parameters and it have been validated by four technology managers from four different large steel mills in Brazil. It became clear that Industry 4.0 implementation is based on technical, organizational and human aspects. The proposed descriptive management model can potentially evolve to an instrument for assessing Industry 4.0 maturity and guide its implementation in the Iron and Steel sector in a structured manner